Differential expression of oxidation-specific epitopes and apolipoprotein(a) in progressing and ruptured human coronary and carotid atherosclerotic lesions - Rogier A. van Dijk; Frank Kolodgie; Amir Ravandi; Gregor Leibundgut; Patrick P. Hu; Anand Prasad; Ehtisham Mahmud; Edward Dennis; Linda K. Curtiss; Joseph L. Witztum; Bruce A. Wasserman; Fumiyuki Otsuka; et al. (Journal of Lipid Research, 2012)
The relationships between oxidation-specific epitopes (OSE) and lipoprotein (a) [Lp(a)] and progressive atherosclerosis and plaque rupture have not been determined. Coronary artery sections from sudden death victims and carotid endarterectomy specimens were immunostained for apoB-100, oxidized phospholipids (OxPL), apo(a), malondialdehyde-lysine (MDA), and MDA-related epitopes detected by antibody IK17 and macrophage markers. The presence of OxPL captured in carotid and saphenous vein graft distal protection devices was determined with LC-MS/MS. In coronary arteries, OSE and apo(a) were absent in normal coronary arteries and minimally present in early lesions. As lesions progressed, apoB and MDA epitopes did not increase, whereas macrophage, apo(a), OxPL, and IK17 epitopes increased proportionally, but they differed according to plaque type and plaque components. Apo(a) epitopes were present throughout early and late lesions, especially in macrophages and the necrotic core. IK17 and OxPL epitopes were strongest in late lesions in macrophage-rich areas, lipid pools, and the necrotic core, and they were most specifically associated with unstable and ruptured plaques. Specific OxPL were present in distal protection devices. Human atherosclerotic lesions manifest a differential expression of OSEs and apo(a) as they progress, rupture, and become clinically symptomatic. These findings provide a rationale for targeting OSE for biotheranostic applications in humans.